Symbiosis, symbolism and the power of the past : Canaan, Ancient Israel and their neighbors : from the late Bronze Age through Roman Palaestina : proceedings of the centennial symposium W. F. Albright Institute of Archaeological Research and American Schools of Oriental Research, May 29-31, 2000, Jerusalem (Winona Lake)
xvii, 596 s.